การเปรียบเทียบช่วงความเชื่อมั่นสำหรับมัธยฐานของการแจกแจงแบบเลขชี้กำลัง - นายพีรณัฐ กองเสียงสังข์ (Mr. Peeranat Kongsiangsang) (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This aim of this study is to compare interval estimation methods for the population median of exponential distribution considering from coverage probabilities and average widths based on the Bayesian method, The inverting a likelihood ratio test method, The variance stabilizing transformation method and the Bayesian bootstrap method. We conducted the simulation studies based on sample sizes of 10, 15, 20, 30, 40, 50, 100, 150 and 200 and population median of 1, 5, 15, 30, 50 and 100. The Monte Carlo simulation is conducted for 10,000 times with 90%, 95% and 99% confidence level for each situation.